Examination of Sharia based Islamic banking Practices and Brand attractiveness of Islamic banking in Pakistan: Customers ’Perspective - Zahid, Misbah; Khan, Dr. Zargham Ullah; Siddiq, Ms. Ujala; Butt, Jaffar Mehmood; Kausar, Dr. Syed Waqas Ali (The journal of contemporary issues in business and government, 2021)
The objective of this study is to identify factors that attract the university students to Islamic bank as compare to conventional banks in Pakistan. Several variables selected after having studied the literature. Among those variables the most important ones are interest free banking, benefits available, service quality, and infrastructure of banks and staff friendliness. But benefits offered are assumed to be constant for this research. In order to undertake the study 100 questionnaires were distributed among the students of Business schools. The response rate was 86 percent. The qualitative research was done to accomplish the study. For the purpose of analysis, descriptive statistical measures and correlation techniques were applied. After getting inside the results, it has been discovered that service quality, Interest free banking and staff friendliness are the variables that attracts the university students to Islamic banks the most. The Islamic bank should improve these factors to increase their share in the market.